Recent Trends in the Marketing Strategies of Life Insurance Corporation of India - Dr.V.S.Rajakrishnan, D.Vanitha, (International Journal of Scientific Research and Management (IJSRM), 2017)
Life Insurance Corporation of India (LIC) is a monolithic company from last few decades. After the successful implementation of economic reforms in life insurance sector in India, LIC of India has made several positive efforts to triumph the hearts of the people. To achieve that LIC of India have adopted a number of new trends in marketing strategies for introducing innovative technologies. This study is an attempt to know about the recent trends followed by LIC of India in order to make their products available to each and every forthcoming customer in the life insurance market. The present research paper is a comprehensive study to know whether the implemented strategies have truly helped LIC of India in the changing trends of the society and will also suggest how these recent trends have helped LIC of India as a whole to manage the existing leading position in the life insurance market